Venous leg ulcer healing as a determinant of quality of life in patients treated with unna boot: A quasi-experimental study - Mário Lins Galvão de Oliveira; Felipe León-Morillas; Isadora Costa Andriola; Carmelo Sergio Gómez Martínez; Bruno Araújo da Silva Dantas; Gilson de Vasconcelos Torres (PLoS ONE, 2025)
Our objective was to assess the effect of Venous Leg Ulcer (VLU) healing on Quality of Life (QoL) in patients undergoing compression therapy. This non-randomized, quasi-experimental, and observational study involved patients with VLU. A convenience sample of individuals receiving services was followed for at least one year while undergoing compression therapy. The Medical Outcomes Short-Form Health Survey (SF-36) and the Charing Cross Venous Ulcer Questionnaire (CCVUQ) were employed to measure the variables of interest. Study participants were categorized into the Healed Group (HG) and the Unhealed Group (UG). The final sample comprised 103 individuals. The HG demonstrated improvements in SF-36 scores in the domains of Social Role Functioning (n = 34, p<0.001), Physical Role Functioning (n = 33, p<0.001), and the Physical Health Dimension (n = 38, p<0.001). Additionally, the CCVUQ assessment revealed score enhancements in the domains of Domestic Activities (n = 30, p = 0.001) and Social Interaction (n = 30, p = 0.009). QoL showed significant improvements in functionality, physical performance, and social interaction in the HG after one year of compression therapy treatment. In contrast, the UG was the only group to experience significant deteriorations in QoL.